Semipurified glycerins on starting piglets feeding‏ (15-30 kg) - doi: 10.4025/actascianimsci.v35i2.17264 - Gonçalves, Liliane Maria Piano; Moreira, Ivan; Furlan, Antonio Claudio; Carvalho, Paulo Levi de Oliveira; Costa Filho, Clodoaldo de Lima; Cruz, Thaline Maira Pachelli da (Acta Scientiarum. Animal Sciences, 2012)
The nutritional value and the performance of piglets fed on diets with semipurified glycerin (SPGV) and mixed (SPGM) vegetable oil was determined and evaluated. Thirty-two crossbred piglets, allotted in a completely randomized block design, were used in the digestibility trial. Two types of glycerin (SPGV and SPGM) and three levels of diet (4, 8 and 12%) were studied. The experimental unit consisted of one piglet. Glycerins’ metabolizable energy (ME) was estimated by regression of ME (kcal kg-1) intake associated with glycerin vs. glycerin intake (kg). ME as-feed-basis rates were 3,373 for SPGV and 2,932 for SPGM, or rather, the glycerins are highly available energy source for piglets. In the performance trial, 90 piglets were allotted in a completely randomized blocks design in a 2 x 4 + 1 factorial scheme, two glycerins, four levels (3, 6, 9 and 12%), five replicates (pens) and two piglets per pen. A control diet with no glycerin (0%) was additionally formulated. Since no effect of glycerin inclusion on pig performance occurred, it was feasible to use up to 12% of both types of glycerin on piglets feeding.